2021
DOI: 10.3389/fphar.2021.669679
|View full text |Cite
|
Sign up to set email alerts
|

Dapsone Ameliorates Isoproterenol-Induced Myocardial Infarction via Nrf2/ HO-1; TLR4/ TNF-α Signaling Pathways and the Suppression of Oxidative Stress, Inflammation, and Apoptosis in Rats

Abstract: Myocardial infarction (MI) is a critical condition that can happen with high doses or rapid termination of beta blockers therapy. The study aimed to evaluate the potential anti-toxic value of DAP against isoproterenol (ISO) - induced MI. Twenty-eight male Wistar rats were used for the study. The rodents were assigned to four groups (n = 7) and the treatments were given for 12 days as follows; Group 1 (control): were administrated normal saline, Group 2 (DAP control): were administrated DAP (10 mg/kg/day IP), G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…The pathological inflammatory process leads to the generation of ROS that damage macromolecules in cardiomyocytes (Abdelzaher et al. 2021 ). Accumulating evidence demonstrate that the Nrf2/HO-1 signalling plays a pivotal role in regulating inflammation (Khalil et al.…”
Section: Discussionmentioning
confidence: 99%
“…The pathological inflammatory process leads to the generation of ROS that damage macromolecules in cardiomyocytes (Abdelzaher et al. 2021 ). Accumulating evidence demonstrate that the Nrf2/HO-1 signalling plays a pivotal role in regulating inflammation (Khalil et al.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is known to contribute to various cardiovascular diseases, including heart failure, myocardial infarct, and reperfusion injury [ 35 , 36 ]. Previous research has also shown that cardiac hypertrophy is related to a reduced cell number due to enhanced apoptosis [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial TNFα and IL1β protein levels were markedly increased in rats treated with two consecutive daily doses of ISO (100 mg/kg/day, i.p.) ( 37 ). Hence, it is very likely that autocrinal or paracrinal TNFα and its activation of TNFR1 mediate the activation of the RIPK1–RIPK3–MLKL pathway by the ISO treatment ( Figure 6 ), although no PubMed searchable studies have tested the requirement of TNFR1 in the induction of cardiomyocyte necrosis by catecholamine surges yet.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium overload and myofibril over-contraction, which can be a direct result of excessive β-adrenergic stimulation from catecholamines and a secondary consequence of I/R injury, may contribute to cardiac dysfunction and injury ( 36 ). Additionally, β-adrenergic stimulation appears to be able to trigger inflammatory responses by upregulating the expression and release of inflammatory cytokines ( 37 ); and many compounds with an anti-inflammatory property can protect against cardiac injury induced by catecholamine surges ( 21 ), suggesting that the secondary injury from inflammation may also play a role in the cardiac injury by catecholamine surges. Necrotic cardiomyocyte death is the most prominent pathological feature of cardiac injury induced by catecholamine surges ( 19 ).…”
Section: Introductionmentioning
confidence: 99%